Use of technology and working conditions in the European Union - Joling, Catelijne; Kraan, Karolus (Luxembourg, 2008)
"Nowadays, technology plays a central role in workplaces, enabling the speedy production of goods and services and facilitating communication and innovation processes. This report examines the different categories of technology used in workplaces in order to gauge their influence on working conditions and health outcomes. The analysis is based on findings from the Fourth Working Conditions Survey carried out across 31 countries, including the 27 EU Member States. The findings reveal that it is not so much the technology itself but rather the associated working conditions that put workers’ health and safety at risk."